An Antidote to the Resource Curse: The Blessing of Renewable Energy - Menegaki, Angeliki N. (International Journal of Energy Economics and Policy, 2013)
<!--[if gte mso 9]> 800x600 <![endif]--> This paper empirically examines the validity of the resource curse in Europe and it is the first time renewable energy is inserted in this research context. The study uses panel data with a variety of explanatory variable proxies for investment, openness, rule of law, resource endowments and human capital. It employs a single equation fixed effects model with heteroskedasticity robust covariance and a simultaneous two equation model where renewable energy enters the structural equation as an endogenous variable. The resource curse is confirmed only for crude oil and resource productivity in the single equation model while renewable energy has a positive relationship to growth. In the simultaneous two equation model, countries with high oil production and emissions also have a higher production of renewable energies. Keywords: Natural resource curse; economic growth, renewable energy; Europe; fixed effects model JEL Classifications; O52; P28; P48; P52; Q20 <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <mce:style><! st1\:*{behavior:url(#ieooui) } --> <!--[endif] --><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif";} --> <!--[endif] -->